2016
DOI: 10.31073/abg.52.19
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Esr1 Gene With Reproductive Traits of Sows of Large White and Mirgorod Breeds

Abstract: The speciality of the modern methodology in breeding is using the molecular information, received during genome analysis. This methodology can significantly accelerate the improvement of productivity traits and it is particularly useful in relation to the traits with low coefficient of inheritance while classic methods are not effective enough. The reproductive traits are one of the most important in pig farming, estrogen receptor 1 gene (ESR1) is involved in their control. Meanwhile, the use of ESR1 locus pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…This feature of the ESR1 gene was confirmed in the work of Distl (2007), where there is a mention of the meta-analysis results obtained by Alfonso (2005) which found in 15 studies on more than 9,000 sows that the B allele is superior for the number of born piglets (total and alive). However, in studies conducted by Balatsky et al (2016) on Mirhorod breed sows the opposite trend was found -sows with the ESR1 AA genotype for first farrowing bore 10.63 ± 0.66 piglets, whereas sows with the ESR1 BB genotype bore 8.83 ± 0.71 piglets. The named authors conclude that under the conditions of their experiment, carriers of the B allele could not realize their genetic potential.…”
Section: Introductionmentioning
confidence: 89%
“…This feature of the ESR1 gene was confirmed in the work of Distl (2007), where there is a mention of the meta-analysis results obtained by Alfonso (2005) which found in 15 studies on more than 9,000 sows that the B allele is superior for the number of born piglets (total and alive). However, in studies conducted by Balatsky et al (2016) on Mirhorod breed sows the opposite trend was found -sows with the ESR1 AA genotype for first farrowing bore 10.63 ± 0.66 piglets, whereas sows with the ESR1 BB genotype bore 8.83 ± 0.71 piglets. The named authors conclude that under the conditions of their experiment, carriers of the B allele could not realize their genetic potential.…”
Section: Introductionmentioning
confidence: 89%